Evaluation of parameters related with upper lip aesthetics and dynamic smile following Le Fort I osteotomy - Dilaver, Emrah; Süzen, Muazzez; Uçkan, Sina (Elsevier, 2022)
Objective: The present study aimed to investigate how upper lip aesthetic and dynamic smile parameters are changed following a Le Fort I osteotomy.Methods: Twenty-seven patients who underwent Le Fort I osteotomy with or without mandibular osteotomy were included in this retrospective study. Upper lip aesthetic parameters which were Cupid's bow angle, lip angle, lip length, lip width, philtrum width and lip corners were evaluated on pre and postoperative rest photos using Image J software. Lip corner movement direction, buccal corri-dor area with respect to canine and last visible tooth were also measured on posed smile photos with respect to dynamic smile evaluations. Measured variables were submitted to statistical analysis and significance level was determined as 0.05.Results: There was a significant reduction in buccal corridor area according to last visible teeth for right and left side at postoperative period. However, buccal corridor area with respect to canine for the right and left side was not significant. The angle between the lip corner movement direction and Y-axis of the face for the right and left sides was not significant between pre and postoperative period. The changes in this angle were not also correlated with the changes in buccal corridor area and maxillomandibular movements. Not only the Cupid's bow angle, lip angle but also lip length, lip width, philtrum width and lip corner have not been changed significantly. Conclusion: Buccal corridor area investigated in dynamic smile shows significant improvement after orthog-nathic surgery especially in the means of maxillary impaction. Lip corner movement during smile was not associated with the changes in buccal corridor area. Landmarks around perioral area in static state were affected clinically with no statistical significance following the surgery.
Keywords: Buccal Corridors; Cupid's Bow Angle; Lip Angle; Lip Corner Movement; Orthognathic Surgery